Acid Inhibitory Effect of a Combination of Omeprazole and Sodium Bicarbonate (CDFR0209) Compared With Delayed‐Release Omeprazole 40 mg Alone in Healthy Adult Male Subjects - Kim, Kyu‐Nam; Yang, Sung‐Won; Kim, Hyunil; Kwak, Seong Shin; Kim, Young‐Sang; Cho, Doo‐Yeoun (Clinical pharmacology in drug development, 2018)
CDFR0209, a combination of an immediate‐release formulation of omeprazole 40 mg and sodium bicarbonate 1100 mg, has been developed to treat acid‐related disorders. We compared the acid inhibitory effects of CDFR0209 and delayed‐release omeprazole (omeprazole‐DR, Losec 40 mg) after repeated dosing in Helicobacter pylori–negative healthy adult male subjects. In this 2‐period crossover study, 30 subjects were randomized to CDFR0209 or omeprazole‐DR daily for 7 days. An ambulatory continuous 24‐hour intragastric pH recording was performed at baseline and on days 1 and 7 of each administration period. Integrated gastric acidity was calculated from time‐weighted average hydrogen ion concentrations at each hour of the 24‐hour record. An analysis of variance model was used to test the pharmacodynamic equivalence of CDFR0209 and omeprazole‐DR, using the natural logarithmic transformation of the percent decrease from baseline in integrated gastric acidity for the 24‐hour interval after the seventh dose of each omeprazole formulation. The geometric least‐squares mean ratios (CDFR0209/omeprazole‐DR) of the percent decrease from baseline in integrated gastric acidity was 0.98 (90%CI, 0.93–1.07). Both CDFR0209 and omeprazole‐DR are equally effective in decreasing integrated gastric acidity at steady state.